Analisis Kebiasaan Belajar dan Hasil Belajar Biologi Siswa kelas XI IPA SMA Negeri 1 Tinambung - Dainur, Nurul Mujahidah; Taiyeb, Mushawwir; Pallennari, Muhiddin (Universitas Negeri Makassar, 2019)
Abstract: This research is descriptive correlational with a simple paradigm research design that aims to find out the correlation between study habits and student learning outcomes. The sample of this study is a saturated sample that is entirely from the population of class XI IPA SMA Negeri 1 Tinambung amounting to 85 students, saturated sample intends to make generalizations with very small errors. Measured study habits include 7 indicators, namely regular Biology learning, preparation for learning in the night, came early to attend the class, conditions / learning atmosphere, learning to understand and to the point, habit of facing exams and practice of visiting the library. The study data of study habits were obtained through a questionnaire and the learning outcomes were obtained from secondary data on the student achievement of the even semester of the 2018/2019 school year which were then processed by Product Moment correlation analysis (r) and the coefficient of determination. The results showed that (1) Study habits of students grade XI IPA SMA Negeri 1 Tinambung is at a good category with an average of 71.98. (2) Biology achievement of student grade XI IPA SMA Negeri 1 Tinambung is found out in high category with an average of 76.12. (3) There is a relationship between the study habits and biology achievement of eleventh grade students at senior high school 1 Tinambung. The correlation level obtained is 11.5% and classified as weak or low correlation. Keywords: student habits, student achievements.